Efficacy of Phytochemical Constituents of Castor Essential oil Towards the Mucor-Mycotic Mold Cunninghamella Bertholletiae - Sheriff Maqbul Muazzam; Badr Saeed Muaadh; Dawoud Areej; Mohammed Tasneem; Abedulla Khan Kayamkani; Rahman Ikbal Abdul; Abdullatif Khan Aejaz; Shakeel Iqubal S.M. (Journal of New Developments in Chemistry, 2020)
The aim of this experiment is to study the efficacy of phytochemical constituents of Castor essential oil towards the mucor-mycotic mold Cunninghamella bertholletiae.The standard chemical analytical methods were used for the rapid study of the phytochemical constituents responsible for the antimicrobial efficacy of the procured castor essential oil. The standard antimicrobial assay technique employed to study the comparative values of the efficacy of the procured castor essential oil with that of the standard antifungal chemical agents against the clinical isolates obtained from the immune suppressed patients samples of Cunninghamella bertholletia mold mucor-mycotic infections. The best susceptibility values recorded in the standard antifungal agents against the clinical isolates of Cunninghamella bertholletiae was with Amphotericin B showing the average zone of inhibition diameter of 20.66 mm with the average MIC value of, 1.66 (µ/ml) but the antimicrobial assay results for the Castor essential oil showed better values with an average disc diffusion of 22.44mm zone of inhibition diameter with average MIC value of 1.72 µ/ml .This study has shown that the phytochemical compounds present in the Castor essential oil proves to be more an effective alternative antifungal substance towards the clinical isolates of Cunninghamella bertholletiae.
Keywords: Castor essential oil